The potential of precision surface irrigation in the Indus Basin Irrigation System - Anwar, Arif A.; Ahmad, W.; Bhatti, Muhammad Tousif; Ul Haq, Z. (Springer, 2016)
In this research we explore the potential of precision surface irrigation to improve irrigation performance under the warabandi system prevalent in the Indus Basin Irrigation System. Data on field dimensions, field slopes along with characteristic soil infiltration properties and outlet discharge were collected through a survey of a sample tertiary unit of Maira Branch Canal, Khyber Pakhtunkhwa Province, Pakistan. The performance of all fields in the tertiary unit was analysed and reported in aggregate, with detailed results of one field presented for illustration. The objective is to determine the optimum field layout, defined as the number of border strips, for the observed field characteristics to maximize performance. The results indicate that performance improvement is relatively easily achievable through changes in field layout within current irrigation services. Estimated application efficiency is sensitive to the selected depth of application, and it is important that a practical depth of application is selected. We recommend a depth of application of 50 mm and show how this is achievable and leads to a low quarter distribution uniformity of 0.750 and an application efficiency of 80 %. We also explore the feasibility of a 10-day warabandi rather than the 7-day warabandi and show that there is no significant change in the performance under a 10-day warabandi.